2020
DOI: 10.1029/2019gl085776
|View full text |Cite
|
Sign up to set email alerts
|

On the Emergence Mechanism of Carrot Sprites

Abstract: We investigate the launch of negative upward streamers from sprite glows. This phenomenon is readily observed in high‐speed observations of sprites and underlies the classification of sprites into carrot or column types. First, we describe how an attachment instability leads to a sharply defined region in the upper part of the streamer channel. This region has an enhanced electric field, low conductivity and strongly emits in the first positive system of molecular nitrogen. We identify it as the sprite glow. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…This region has low conductivity, and the electrons are converted to negative ions which intensifies the electric field and maximises photon production. 32 From our analysis, we found that the altitude of maximum brightness ranges between 53.5 km and 84.1 km. The average maximum brightness altitude was found to be about 69 km with a standard deviation of 6.2 km.…”
Section: Distribution Of the Altitudes Of Maximum Sprite Brightnessmentioning
confidence: 68%
See 1 more Smart Citation
“…This region has low conductivity, and the electrons are converted to negative ions which intensifies the electric field and maximises photon production. 32 From our analysis, we found that the altitude of maximum brightness ranges between 53.5 km and 84.1 km. The average maximum brightness altitude was found to be about 69 km with a standard deviation of 6.2 km.…”
Section: Distribution Of the Altitudes Of Maximum Sprite Brightnessmentioning
confidence: 68%
“…The altitudes of maximum brightness for column and carrot sprites are in agreement with those reported in the literature. 15,31,32 The altitude of maximum brightness also does not depend on the time of the event. From the literature, the altitude of maximum brightness region lies between 65 km and 85 km.…”
Section: Distribution Of the Altitudes Of Maximum Sprite Brightnessmentioning
confidence: 99%
“…Kochkin et al (2012) captured images where a positive streamer corona triggers negative streamers as it approaches an electrode. The same group found positive streamers emerging from the channels of preceding negative streamers (Kochkin et al, 2014) and a similar process explains the shape of carrot sprites in the upper atmosphere (Malagón-Romero et al, 2020). In the numerical simulations of Malagón-Romero et al (2020), similar currents flow through the channels of the downward and upward streamers because they are connected through electrically conducting regions.…”
Section: Discussionmentioning
confidence: 69%
“…( 2012 ) captured images where a positive streamer corona triggers negative streamers as it approaches an electrode. The same group found positive streamers emerging from the channels of preceding negative streamers (Kochkin et al., 2014 ) and a similar process explains the shape of carrot sprites in the upper atmosphere (Malagón‐Romero et al., 2020 ). In the numerical simulations of Malagón‐Romero et al.…”
Section: Discussionmentioning
confidence: 82%
“…In the numerical simulations of Malagón‐Romero et al. ( 2020 ), similar currents flow through the channels of the downward and upward streamers because they are connected through electrically conducting regions.…”
Section: Discussionmentioning
confidence: 99%